Leveraging technology adoption model for examining internet usage among physicians' in changing Indian pharmaceutical marketing context: A structural equation modeling approach. (November 2014) - Patwardhan, Avadhut Arun; Pandey, Neeraj; Dhume, SM
Considering technological advancements happening all across the globe, the internet has been incorporated as an emerging medium of pharmaceutical promotion by Organization of Pharmaceutical Producers of India in the year 2012. In Indian pharmaceutical industry, the marketing process is only physician directed (except for "over-the-counter" drugs) and Direct to Consumer Advertising using internet or any other means of marketing communication is legally not allowed. Therefore, the knowledge about adoption and usage pattern of internet among Indian physician needs to be examined. This understanding would help the pharmaceutical marketing organizations to better promote their products over internet to the target customers, i.e. physicians. The present research describes about physicians' technology acceptance phenomenon based on theoretical concept of technology adoption model. The structural equation model analysis highlighted relevance of technology adoption model to examine physicians' internet adoption phenomenon in changing Indian pharmaceutical marketing context. The research also cautions that actual usage of internet by physicians and specialists should be analyzed separately for professional activities and for personal activities in order to get accurate marketing insights.